Review of mathematical models of HSV-2 vaccination: Implications for vaccine development - Spicknall,I; Looker,K; Gottlieb,S; Chesson,H; Schiffer,J; Elmes,J; Boily,MC (Vaccine, 2019)
Development of a vaccine against herpes simplex virus type 2 (HSV-2), a life-long sexually-transmitted infection (STI), would be a major step forward in improving global sexual and reproductive health. In this review, we identified published literature of dynamic mathematical models assessing the impact of either prophylactic or therapeutic HSV-2 vaccination at the population level. We compared each study’s model structure and assumptions as well as predicted vaccination impact. We examined possible causes of heterogeneity across model predictions, key gaps, and the implications of these findings for future modelling efforts. Only eight modelling studies have assessed the potential public health impact of HSV-2 vaccination, with the majority focusing on impact of prophylactic vaccines. The studies showed that even an imperfect prophylactic HSV-2 vaccine could have an important public health impact on HSV-2 incidence, and could also impact HIV indirectly in high HIV prevalence settings. Therapeutic vaccines also may provide public health benefits, though they have been explored less extensively. However, there was substantial variation in predicted population-level impact for both types of vaccine, reflecting differences in assumptions between model scenarios. Importantly, many models did not account for heterogeneity in infection rates such as by age, sex and sexual activity. Future modelling work to inform decisions on HSV vaccine development and implementation should consider cost-effectiveness, account for additional HSV-2 sequelae such as neonatal transmission, and model greater heterogeneity in infection rates between individuals, more realistic vaccine deployment, and more thorough sensitivity and uncertainty analyses.